KEWAJIBAN PERPAJAKAN PASCA PP 23/2018: SIAPKAH WAJIB PAJAK MELAKSANAKANNYA? - Dian Purnama Sari; Patricia Febrina Dwijayanti; Rwa Abimantrana Ksemadyastu; Michael Michael (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2022)
This study is to empirically test the readiness of Corporate Taxpayers to carry out tax obligations after Government Regulation number 23/2018 (PP 23/2018). The survey method is an appropriate method for this research. Respondents as the object of this research are MSME owners in East Java, in the form of a CV and calculating Income Tax based on PP 23/2018. The results of this study indicate that tax socialization, taxpayer knowledge and tax sanctions have a positive effect on readiness to carry out tax liability after PP 23/2018. Interestingly, awareness of tax compliance does not affect the readiness of taxpayers to carry out their tax liability after PP 23/2018.